Pro JSP 2, Fourth Edition - Brown, Simon (Apress, 2012)
This book is aimed at anyone who knows the Java language and core APIs and wants to learn about web programming with the latest versions of the JSP and Servlet APIs. Familiarity with HTML is required; however, no prior knowledge of server-side Java programming is necessary. Having said that, this book does not claim to be exhaustive in all areas, particularly in relation to other Java Enterprise Edition APIs such as Enterprise JavaBeans.